Gender Differentiation by Articulated Pelvic Index: A Radiological Study Over the Population of Bihar (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
Introduction: Identification is the establishment of the identity of a person with the help of different physical characteristics.The different physical characteristics of the human skeleton between both the genders is the reason for Sexual dimorphism. Many researchers have studied and observed the different parameters for sexual dimorphism in different bones. Pelvis is the most important bone for determination of gender because the sexual dimorphism is present even in the fetal stage. In the modern era of advancement, pathological autopsy is shifting towards the virtual autopsy in which CT scan, MRI and X-rays are replacing the conventional autopsy instruments. Aims and Objective: To establish gender differentiation criteria in the population of Bihar based on Articulated Pelvic index. Methodology: we used 200 antero-posterior views of pelvic digital radiograph, equal from both genders. Through digital radiograph of pelvis we measured maximum length of pelvic bone between summit of iliac crest to ischial tuberosity and maximum width of pelvic bone between two anterior superior iliac spine with DICOM software and calculated articulated pelvic index. Observation and Results: Articulated pelvic index of pelvis in male and female gender is 133.96 with SD 11.47 and 133.96 with SD 11.47 respectively. Conclusion: females had significantly higher mean value of articulated pelvic index than males.
Keywords: Anterior superior iliac spine; Articulated pelvic index; Iliac crest; Ischial tuberosity; Pubis; Sexual dimorphism